Health insurance: Treatment vs. compensation - Geir B. Asheim; Anne Wenche Emblem; Tore Nilssen (University of Oslo, Department of Economics, 2000)
In this paper, we view health insurance as a combined hedge against the two consequences of falling ill: treatment expenditures and loss in income. We discuss how an individual's ability when healthy affects her decision on whether to buy health insurance with treatment to full recovery if ill or with partial treatment combined with cash compensation for the resulting loss in income. We find that a high ability individual demands full recovery and is fully insured, while a low-ability individual demands partial treatment and cash compensation and is only partly insured.
Keywords: I11; G22; D81; 330; Krankenversicherung; Versicherungsökonomik; Theorie